Effect of Conidiobolus coronatus on the Cuticular and Internal Lipid Composition of Tettigonia viridissima Males. Issue 8 (12th August 2016) - Gołębiowski, Marek; Cerkowniak, Magdalena; Ostachowska, Aleksandra; Naczk, Aleksandra M.; Boguś, Mieczysława I.; Stepnowski, Piotr
Abstract : Conidiobolus coronatus is an entomopathogenic fungus which has a potential as a biological control agent of insects. The cuticular and internal lipid composition of infected and noninfected Tettigonia viridissima males were analyzed by GC/MS. A total of 49 compounds were identified in the infected and noninfected males, including fatty acids, fatty acid methyl esters (FAMEs), n ‐alkanes, alcohols, sterols, and other organic compounds. The most abundant components of the cuticular and internal lipids of the insects were fatty acids. After exposure to C. coronatus, the cuticular lipids of the T. viridissima males contained 17 free fatty acids from C(8) to C(22), while the cuticular lipids of the noninfected insects contained only 15 fatty acids from C(12) to C(24). The cuticular and internal lipids of both the infected and the noninfected males also contained five FAMEs from C(15) to C(19), seven n ‐alkanes from C(25) to C(34), five alcohols from C(16) to C(25), five sterols, and the following six other organic compounds: azelaic acid, phenylacetic acid, glutaric acid, benzoic acid, sebacic acid, and glycerol. The compounds which were present only in the cuticular lipids of the infected males could be due to fungal infection. Abstract : Effect of Conidiobolus coronatus on the Cuticular and Internal Lipid Composition of Tettigonia viridissima Males. M. Gołębiowski*, M. Cerkowniak, A. Ostachowska, A. M. Naczk, M. I. Boguś, P. Stepnowski